Review of Interventional Therapies for Refractory Pediatric Migraine - Jacquelin Peck; Justin Zeien; Megha Patel; Elyse M. Cornett; Amnon A. Berger; Jamal Hasoon; Hisham Kassem; Jai Won Jung; Giovanni F. Ramírez; Paola Colon Fugueroa; Neil R. Singhal; Jaehong Song; et al. (Health Psychology Research)
This is a review of the latest and seminal evidence in pediatric migraine. It covers the etiology and pathophysiology known today, and then will review treatment options, efficacy and safety, quality of data and indications. Though migraine is usually regarded as an infliction in adults, it is not uncommon in the pediatric population and affects up to 8% of children. Children may experience migraine differently than adults, and present not only with headache but also frequent gastrointestinal symptoms. They are frequently shorter in duration than in adults. Traditional migraine treatment in adults is less effective in children. In this population, adjunct therapies -- such as interventional techniques -- should be considered when traditional treatment fails, including Botulinum Toxin A (BTA) injections, peripheral nerve and ganglion blocks. BTA injections are FDA approved for migraine prophylaxis in adults, but currently not in children; however, recent evidence shows efficacy and safety in pediatric migraine management. Nerve blocks stop nociceptive afferent fibers through injection of local anesthetics, and it may be associated with the local injection of corticosteroids. Although more common in adults, recent data suggests they are safe and effective in children and adolescents. Blocking the sphenopalatine ganglion can be achieved through nasal approach, and achieves a similar action by blocking the entire ganglion. Interventional techniques may provide a key component in the alleviation of this otherwise debilitating chronic migraine pain. Though most studies have been performed in adults, new studies provide encouraging results for treatment in children.